Diagnostic Accuracy of Early Secretory Antigenic Target-6–Free Interferon-gamma Release Assay Compared to QuantiFERON-TB Gold In-tube. (21st January 2019) - Nemes, Elisa; Abrahams, Deborah; Scriba, Thomas J; Ratangee, Frances; Keyser, Alana; Makhethe, Lebohang; Erasmus, Mzwandile; Mabwe, Simbarashe; Bilek, Nicole; Rozot, Virginie; Geldenhuys, Hennie; Hatherill, Mark; et al.
Abstract: Background: Early secretory antigenic target-6 (ESAT-6) is an immunodominant Mycobacterium tuberculosis (M.tb) antigen included in novel vaccines against tuberculosis (TB) and in interferon-gamma (IFN-γ) release assays (IGRAs). Therefore, the availability of an ESAT-6–free IGRA is essential to determine M.tb infection status following vaccination with ESAT-6–containing vaccines. We aimed to qualify a recently developed ESAT-6–free IGRA and to assess its diagnostic performance in comparison to QuantiFERON-TB Gold In-tube (QFT). Methods: Participants with different levels of M.tb exposure and TB disease were enrolled to determine the ESAT-6–free IGRA cutoff, test assay performance in independent cohorts compared to standard QFT, and perform a technical qualification of antigen-coated blood collection tubes. Results: ESAT-6–free IGRA antigen recognition was evaluated in QFT-positive and QFT-negative South African adolescents. The ESAT-6–free IGRA cutoff was established at 0.61 IU/mL, based on receiver operating characteristic analysis in M.tb-unexposed controls and microbiologically confirmed pulmonary TB patients. In an independent cohort of healthy adolescents, levels of IFN-γ released in QFT and ESAT-6–free IGRA were highly correlated (P < .0001, r = 0.83) and yielded comparable positivity rates, 41.5% and 43.5%, respectively, with 91% concordance between the tests (kappa = 0.82; 95% confidence interval, 0.74–0.90; McNemar test P = .48). ESAT-6–free IGRA blood collection tubes had acceptable lot-to-lot variability, precision, and stability. Conclusions: The novel ESAT-6–free IGRA had diagnostic accuracy comparable to QFT and is suitable for use in clinical trials to assess efficacy of candidate TB vaccines to prevent established M.tb infection. Abstract : The novel early secretory antigenic target-6 (ESAT-6)–free interferon-gamma release assay has comparable diagnostic performance for Mycobacterium tuberculosis (M.tb) infection as the QuantiFERON-TB Gold assay and is suitable for diagnosing M.tb infection in clinical trials of ESAT-6–containing tuberculosis vaccines.